Parents Adolescent communication on sexual health and behaviour in Anfoega North Dayi - Adofoli, G.M. (University of Ghana, 2018)
Background: Adolescents who are active sexually involve themselves in acts that are risky to their sexual health including an increasingly premature age of sexual growth, the absence of sex information, decreasing cultural and religious impacts, urbanisation and growing numbers of early marriages. The purpose of this study was to examine parent – adolescent communication on sexual health and behaviour in Anfoega in the North Dayi District of the Volta Region. Methodology: A quantitative cross-sectional study design was used. A multistage sampling design which included proportionate sampling, systematic sampling and simple random sampling was employed to select 290 respondents for questionnaire completion. Descriptive and inferential statistical analysis was performed. Results: The results showed that there is good receiving of sex education (46.2%) by adolescents from parents. The results also revealed that majority of the adolescents (60.3%) have knowledge of contraceptives and 85.91% of them know of condoms with only 4.1% claiming to have engaged in premarital sex. Most (32.4%) of the adolescents first heard of sex from their friends and 53.4% are influenced by their peers to engage in premarital sex. Finally, there was a statistically significant positive relationship between parent-adolescent communication and receiving of sex education. Conclusion: Interventions such as capacity building, and taking responsibility for adolescent sex education are needed by the family, schools, government and the entire society in order to enhance parent adolescent communication on sexual health and behaviour.
MSc.
Keywords: sexual health; Anfoega North Dayi; parent – adolescent; communication